Study granulometric and their application to the industrial processes of cork residuals and cork of low quality - Antonio Macías García; Ángel Hernández Jiménez; Javier Hernández Santiago (Ingeniería e Investigación, 2003)
Granulometric study of form and size of the particles of black re-granulated of cork residuals and low quality cork, have a great interest because it influences the proportion of resin and neccesary cork for the formation of bound black regranulates by means of the use of natural resin / busresin) as of different synthetic resins and in their applicaion in projection teams of commercial particles for the formation of uniform films with a more economic cost. In accordance with the results obtained in this and another works, it is recommended like good values of the particles a hald size among (1-2,5) mm, since minimizes the effect it bounces and the quantity of resin so much natural as synthetic what allows a degree of good compactin. Everything it, supposes to improve the industrial applications and to optimize the use of commercial teams of projections of cork particles to obtain uniform movies in surfaces (insulating thermal or acoustic).